A review of the genus Compterosmittia Sæther, 1981 (Diptera: Chironomidae) from China - Lin, Xiaolong; Yao, Yuanyuan; Liu, Wenbin; Wang, Xinhua (Zootaxa, 2013)
The genus Compterosmittia Sæther, 1981 from China is reviewed. Three new species, C. duodecima sp. n., C. lii sp. n. and C. procera sp. n. are described as adult males. C. nerius (Curran, 1930), C. oyabelurida (Sasa, Kawai et Ueno, 1988) and C. togalimea (Sasa et Okazawa, 1992) are recorded from China for the first time and annotated; as a result the diag-nosis for the genus is emended. A key to adult males of all known Compterosmittia is also presented.